2022
DOI: 10.3390/molecules27051492
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Phenylacetaldehyde in Wine: Application of a Microwave Sensor Based on Molecularly Imprinted Silica

Abstract: Molecularly imprinted sol–gel silica (MIS) coupled to a microwave sensor was designed and used to detect phenylacetaldehyde (PAA), a chemical tracer of wine oxidation. The developed method is fast, cheap and could replace the classical chromatographic methods, which require a tedious sample preparation and are expensive. To reach our objective, five MIS and their control non-imprinted silica (NIS) were synthesized and their extraction capacity toward PAA was studied in hydro alcoholic medium. The selected poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Primarily formed by the oxidation of 2-PE, P.A. is used as a chemical indicator for oxidation levels in wine; the detection and prevention of the formation of phenylacetaldehyde are currently being researched [72].…”
Section: Phenolicsmentioning
confidence: 99%
“…Primarily formed by the oxidation of 2-PE, P.A. is used as a chemical indicator for oxidation levels in wine; the detection and prevention of the formation of phenylacetaldehyde are currently being researched [72].…”
Section: Phenolicsmentioning
confidence: 99%
“…Rossignol et al [ 7 ] developed a microwave sensor based on molecularly imprinted silica for the real-time detection of phenylacetaldehyde in wine. They concluded that the developed sensor based on molecularly imprinted sol–gel silica (MIS) coupled to a microwave sensor was able to detect phenylacetaldehyde (PAA), a chemical tracer of wine oxidation, at the µg/L level, which is below the off-flavour threshold of PAA in red wine.…”
Section: Highlights Of the 16th Editionmentioning
confidence: 99%